Numerical simulation of the effective permittivity of low‐density polyethylene composite filled by carbon black. Issue 4 (26th July 2019) - Azizi, Sohrab; David, Éric; Fréchette, Michel F.; Ouellet‐Plamondon, Claudiane M.
Abstract : The effective permittivity of low‐density polyethylene with the conductive carbon black (CB) was modelled by COMSOL. The impact of CB content on the electric properties of the composites with different geometry of the inclusions was investigated. The modelling outcomes evidenced that the simulation was in good agreement with the experiment results at low‐filler concentration. The effect of moisture on the effective permittivity of the composites was also investigated. A thin layer of adsorbed water on the surface of the CB particles was found to significantly increase the conductivity, which is in agreement with experimental results.